Gaze During Locomotion in Virtual Reality and the Real World - Drewes, Jan; Feder, Sascha; Einhäuser, Wolfgang (Frontiers in Neuroscience, 2021)
How vision guides gaze in realistic settings has been researched for decades. Human gaze behavior is typically measured in laboratory settings that are well controlled but feature-reduced and movement-constrained, in sharp contrast to real-life gaze control that combines eye, head and body movements. Previous real-world research has shown environmental factors such as terrain difficulty to affect gaze; however, real-world settings are difficult to control or replicate. Virtual reality (VR) offers the experimental control of a laboratory, yet approximates the freedom and visual complexity of the real world (RW). We compared gaze between walking in the RW and simulated locomotion in VR. Participants walked along a pre-defined path inside an office building, which included different terrains such as long corridors and flights of stairs. In VR, participants followed the same path in a detailed virtual reconstruction of the building. We devised a novel hybrid control strategy for movement in VR: participants did not actually translate – forward movements were controlled by a hand-held device – but rotational movements were executed physically and transferred to the VR. We found significant effects of terrain type (flat corridor, staircase up, staircase down) on gaze direction, on the spatial spread of gaze direction, and on the angular distribution of gaze-direction changes. The factor world (RW, VR) affected only the angular distribution of gaze-direction changes and vertical gaze direction in head-centered coordinates. The latter effect vanished when gaze was referenced to a world-fixed coordinate system, and was likely due to specifics of headset placement, which cannot confound any other analyzed measure. Importantly, we did not observe a significant interaction between the factors world and terrain for any of the tested measures. This indicates that differences between terrain types are not modulated by the world. The overall dwell time on navigational markers did not differ between worlds. The similar dependence of gaze behavior on terrain in the real world and in VR indicates that our VR captures real-world constraints remarkably well. High-fidelity VR combined with naturalistic movement control therefore has the potential to narrow the gap between the experimental control of a lab and ecological valid settings.